Praktik Pengelolaan APBDes dalam Pandangan Aparatur dan Masyarakat Desa Sidamukti - Meisya Ayu Azhara; Nadifha Tiara Safitri; Adizka Azzahra Aurian; Asri Wulandari; Dafinsyah Fathir Abrar (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
The Village Revenue and Expenditure Budget (APBDes) serves as a key component of village administration, as it guides development priorities and the provision of public services. This study examines the implementation of APBDes management in Sidamukti Village, Baros District, Serang Regency, from the perspectives of both village officials and local residents. Using a descriptive qualitative design with a case study approach, data were gathered through interviews, observations, and document analysis involving village government representatives, community leaders, youth representatives, and residents. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings reveal that APBDes management has generally incorporated the principles of participation, transparency, and accountability. Community involvement is evident through participation in village deliberation meetings, although attendance and active engagement remain relatively limited. Transparency efforts have been carried out through public meetings, information boards, and other communication channels, yet some residents still face difficulties in understanding the information presented. In terms of accountability, financial administration and reporting have been conducted in line with applicable regulations, although public access to accountability information could be improved. Several challenges were identified, including limited public participation, inadequate understanding of APBDes management among residents, and budget limitations that require the village government to prioritize certain development programs. As a result, not all community needs can be fully accommodated. Strengthening public participation, expanding the use of information technology, and improving transparency and accountability are therefore essential to support more effective village governance.